International Workshop on Wearable and Implantable Body Sensor Networks (BSN'06)
DOI: 10.1109/bsn.2006.6
|View full text |Cite
|
Sign up to set email alerts
|

Activity Recognition and Monitoring Using Multiple Sensors on Different Body Positions

Abstract: The design of an activity recognition and monitoring system based on the eWatch, multi-sensor platform worn on different body positions, is presented in this paper. The system identifies the user's activity in realtime using multiple sensors and records the classification results during a day. We compare multiple time domain feature sets and sampling rates, and analyze the tradeoff between recognition accuracy and computational complexity. The classification accuracy on different body positions used for wearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
213
0
6

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(236 citation statements)
references
References 5 publications
2
213
0
6
Order By: Relevance
“…Battery lifetime estimations in a indicative scenario demonstrate the dependency of the battery lifetime to the configuration settings of the accelerometers (estimations range from weeks to years). For example, assuming 210 mAh battery capacity, a configuration used in [16] yields a battery lifetime estimation of 240 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Battery lifetime estimations in a indicative scenario demonstrate the dependency of the battery lifetime to the configuration settings of the accelerometers (estimations range from weeks to years). For example, assuming 210 mAh battery capacity, a configuration used in [16] yields a battery lifetime estimation of 240 days.…”
Section: Resultsmentioning
confidence: 99%
“…Social studies [27][3] have shown the importance of wearable devices being comfortable and not intrusive to the daily life activities. In [16], the authors assess various body positions and present comparison results in which the wrist ranks high in all the considered activities in terms of classification accuracy. The core component is a nRF51822 system-on-chip (SoC) which incorporates a ARM Cortex M0 microcontroller unit (MCU), 32KB of RAM, 256KB of non-volatile flash memory, and a BLE radio (a comparison study of BLE and ZigBee can be found in [20]).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A ``ewatch" device is placed in shirt pocket, trouser pocket, backpack etc. to recognize the common user activities, with the use of bi-axial accelerometer and light sensor by Maurer et al [16]. Choudhury et al [8] used a model consisting of seven different sensors to recognize activities.…”
Section: Related Workmentioning
confidence: 99%
“…Previous works have shown that, machine learning algorithms are efficient for human movement classification. Khan [4,5]. It was the main motivation to use those three machine learning methods in this study.…”
Section: Copyright © 2006-2017 By CCC Publicationsmentioning
confidence: 99%